Lewis‐Acidic PtIr Multipods Enable High‐Performance Li–O2 Batteries. Issue 51 (17th November 2021) - Zhou, Yin; Yin, Kun; Gu, Qianfeng; Tao, Lu; Li, Yiju; Tan, Hao; Zhou, Jinhui; Zhang, Wenshu; Li, Hongbo; Guo, Shaojun
Abstract: The sluggish oxygen reaction kinetics concomitant with the high overpotentials and parasitic reactions from cathodes and solvents is the major challenge in aprotic lithium‐oxygen (Li–O2 ) batteries. Herein, PtIr multipods with a low Lewis acidity of the Pt atoms are reported as an advanced cathode for improving overpotentials and stabilities. DFT calculations disclose that electrons have a strong disposition to transfer from Ir to Pt, since Pt has a higher electronegativity than Ir, resulting in a lower Lewis acidity of the Pt atoms than that on the pure Pt surface. The low Lewis acidity of Pt atoms on the PtIr surface entails a high electron density and a down‐shifting of the d‐band center, thereby weakening the binding energy towards intermediates (LiO2 ), which is the key in achieving low oxygen‐reduction‐reaction (ORR) and oxygen‐evolution‐reaction (OER) overpotentials. The Li–O2 cell based on PtIr electrodes exhibits a very low overall discharge/charge overpotential (0.44 V) and an excellent cycle life (180 cycles), outperforming the bulk of reported noble‐metal‐based cathodes. Abstract : PtIr multipods with low Lewis acidity of the Pt atoms are reported as an advanced cathode for high‐performance Li–O2 batteries. The low Lewis acidity of the Pt atoms on the PtIr surface entails a down‐shifting of the d‐band center, which brings low oxygen‐reduction‐reaction and oxygen‐evolution‐reaction overpotentials.